Optimization of spatial configurations of radio-navigation system location - Беляевский Л. C.; Сушич, А. П.; Шешин, И. Ф. (Proceedings of National Aviation University (archive), 2000)
Proposed is a new approach to substantiation of spatial location of radio-navigation subsystem, which optimize the accuracy of consumer location. Worked out are some criteria based on the use of the theory of optimal information encoding which are dimensions near to optimum in constructing quasi-optimal spatial structures of multi-positional complexes of radio-navigation systems